Photocatalytic degradation of amoxicillin by carbon quantum dots modified K2Ti6O13 nanotubes: Effect of light wavelength - Qiankun Chen; Long Chen; Juanjuan Qi; Yingqian Tong; Yitao Lv; Chaokai Xu; Ni, Jinren; Liu, Wen (Chinese Chemical Letters, 2019)
A novel carbon quantum dots modified potassium titanate nanotubes (CQDs/K2Ti6O13) composite photocatalyst was synthesized by hydrothermal treatment combined with calcination. X-ray diffraction (XRD) pattern and transmission electron microscopy (TEM) indicated formation of potassium titanate nanotubes and successful deposition of CQDs onto K2Ti6O13. The photocatalytic performance of CQDs/K2Ti6O13 composite was evaluated by degradation of amoxicillin (AMX) under the irradiation of visible light and lights with the wavelengths of 365, 385, 420, 450, 485, 520, 595 and 630 nm. The results showed that the photocatalytic activity of CQDs/K2Ti6O13 hybrid material was greatly enhanced compared with the neat K2Ti6O13 calcined at 300 °C. The narrowed band gap energy (Eg) and transfer of photo-excited electron by CQDs inhibited the immediate combination of electron-hole pairs, thus promoting photocatalytic activity. Moreover, CQDs/K2Ti6O13 exhibited a broad spectrum of photocatalytic ability and it was interesting that the photocatalytic activity decreased with the increase of the irradiation wavelength. Reactive oxygen species (ROS) quenching tests suggested the hole (h+) and hydroxyl radical (OH) played the primary roles in photocatalytic degradation of AMX. Moreover, CQDs/K2Ti6O13 showed good reusability for AMX photocatalytic degradation after five successive runs. This study proposed an available method for titanate nanomaterials modification, and the developed novel CQDs/K2Ti6O13 hybrid material is promising for potential application on antibiotics removal from water and wastewater.
Keywords: Antibiotics; Carbon quantum dots; Photo energy; Photocatalysis; Potassium titanate nanotubes